Pembentukkan Karakter Religius Siswa Kelas VIII Melalui Kegiatan Shalat Dhuha di SMP NU Simo - Eka Nur Hidayati; Khotimah Suryani; Mahbub Junaidi (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
Religious education has an important role in shaping the character of students, especially religious character which is the moral foundation in life. The habit of worship, such as the dhuha prayer, is one of the concrete efforts made by schools to instill religious values in students. At SMP NU Simo, dhuha prayer activities are made a routine before learning begins as a means of forming students' religious character. However, in its implementation, there are still several obstacles, such as the lack of discipline of some students in participating in the dhuha prayer, low awareness of the importance of this sunnah worship, the influence of the environment and peers who are less supportive, and the lack of variety of coaching methods that make some students carry out worship only as a formal obligation without understanding its meaning in depth. The results of the study show that the dhuha prayer activities carried out regularly at SMP NU Simo are able to form students' religious character, such as discipline, responsibility, and spiritual awareness. Students become more accustomed to carrying out worship independently and have an attitude that reflects the value of religious values in daily life. Inhibiting factors in the implementation of this activity include lack of student awareness, environmental influences, as well as limited time and teacher supervision. Keywords: Formation, Religious Character, Dhuha Prayer.